DISIPLIN WARGA BELAJAR PAKET B DALAM KEGIATAN BELAJAR MENGAJAR PADA PKBM HARAPAN BANGSA DI DESA TARAI BANGUN KECAMATAN TAMBANG KAB. KAMPAR - ', Radiansyah; Maemunaty, Titi; Jas, Jasfar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on the state of the Discipline learn the study in studying to a package B di PKBM Harapan Bangsa di Kubang Raya Kecamatan Tambang Kab.Kampar seen from learn discipline. Because of the Learn the discipline is the condition of being created and formed through the process and a series of behavior that shows residents learn values in following learning activities on packages B di PKBM Harapan Bangsa di Kubang Raya Kecamatan Tambang Kab.Kampar. The formulation the research is how high levels of discipline learn the study in following the teaching and learning process to a package packages B di PKBM Harapan Bangsa di Kubang Raya Kecamatan Tambang Kab.Kampar?. The purpose of this research is to find discipline learn the study in studying to a package B di PKBM Harapan Bangsa di Kubang Raya Kecamatan Tambang Kab.Kampar. Population in this study as many as 48 people. Then the researcher determine samples from 48 people for research and 20 people to the tests of somewhere else, with uses the technique of sampling saturated. An instrument data collection namely poll with 48 a statement and if the trial live 40 a statement that valid to make instrument in research. Through data analysis of the quantitative descriptive analysis. So, the research results show discipline residents learning packages B dalam kegiatan belajar mengajar pada PKBM Harapan Bangsa Di Desa Tarai Bangun Kecamatan Tambang Kab. Kampar who with a large percentage a whole the average (SS+S) 76%. So that discipline residents learn package B In learning activities in PKBM Harapan Bangsa Di Desa Tarai Bangun Kecamatan Tambang Kab. Kampar is considered to be higher.Key words: Discipline, discipline residents learn package B In learning activities